(untitled) (Journal of Economics and Sustainability, 2021)
The study seeks to ascertain the effect of tax avoidance on the accounting conservatism of listed non-financial firms in Nigeria. Tax avoidance was proxied by Generally Accepted Accounting Principle Effective Tax Rate (GETR), Cash Effective Tax Rate (CETR), and Book Tax Difference (BTD), while accounting conservatism was measured using Negative Accruals (NA). The control variables utilised were leverage, Return on Asset (ROA), and Firm Size (FS). The study covered a period of seven years (2014-2020) and a population of forty-eight listed non-financial firms on the Nigerian stock exchange. The data were analysed using the panel regression technique. The findings discovered that GETR and BTD significantly and negatively affect unconditional conservatism. Overall, this paper shows that tax avoidance is a determinant of financial reporting conservatism in Nigeria.